Qualitative Study Of Omnichannel Marketing Strategy On Product Repurchasing Decision (Case Study on Alfamart Retail Company) - Antasari, Dewi Wungkus; Selviasari, Diana Ambarwati, Rike (YUME : Journal of Management, 2025)
This study examines the implementation of omnichannel marketing strategies in influencing customer’s repurchase decisions, with a focus on the Alfagift application developed by Alfamart. The COVID-19 pandemic has significantly accelerated digital transformation in the retail sector, encouraging companies to integrate online and offline services in innovative ways. This study is a qualitative approach through surveys and interviews, this research analyzes how Alfagift enhances the consumer experience through key features such as an informative product catalog, flexible payment methods, efficient delivery services, and digital transaction tracking. The results show that Alfagift not only improves operational efficiency but also strengthens customer loyalty by offering a seamless and personalized shopping experience. The study concludes that effectively implemented omnichannel strategies play a crucial role in increasing customer satisfaction and driving repeat purchases in the digital retail ecosystem. Keywords: Omnichannel marketing, Alfagift, repurchase decision, digital transformation, consumer behavior.